Glass Ceiling Perception and Its Role in Women Employees Turnover Intention in Insurance Industry - Chaudhary, Manoj Kumar; Dhungana , Madan; Timilsina, Jagat; Dahal , Asmita (International Research Journal of MMC, 2025)
This study examines the effect that glass ceiling perceptions have on female employees' intention to leave life insurance companies in the Kathmandu Valley. As part of a cross-sectional explanatory study design, data from 252 female employees was collected in January 2025 using a purposive sampling technique through a structured questionnaire. Employee relations, lack of organizational support, discriminatory promotion practices, and family obligations were all examined in relation to turnover intention. The results of the correlation study showed that employee relations, organizational support, and discriminatory promotion practices were significantly correlated with the intention to leave. Employee relations negatively correlated (-0.178, P < 0.05) with turnover intention. In contrast, discriminatory promotion practices had a positive correlation (0.320, P < 0.01), and regression analysis verified that discriminatory promotion practices, family obligations, and a lack of organizational support significantly impacted this intention. According to these results, lowering turnover intention and raising organizational commitment among women in the insurance industry require removing glass ceiling barriers, advancing gender equality, and fostering better employee relations. The study implies the need for diversity initiatives, transparent promotions, mentorship programs, and addressing gender biases in organizations.